The monastery of Epiphanius at Thebes ... - Winlock, Herbert E. (Publications of the Metropolitan museum of art Egyptian expedition / edited by A. M. Lythgoe, 1926)
I. The archaeological material, by H. E. Winlock. The literary material, by W. E. Crum.--II. Coptic ostraca and papyri, edited with translations and commentaries by W. E. Crum. Greek ostraca and papyri, edited with translations and commentaries by H. G. Evelyn White.